2016
DOI: 10.1149/2.0461614jes
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Overpotentials in Lithium Ion Batteries: A Case Study on the LiNi1/3Co1/3Mn1/3O2(NCM) Cathode

Abstract: The practically available specific energy of Li ion batteries (LIB) is highly depending on the used specific charge/discharge current, since the respective overpotentials of each electrode affect the two vital specific energy parameters, specific capacity and voltage. Focusing on the positive composite electrode as the specific energy bottleneck, the overall nature of the overpotential is discussed for the LiNi 1/3 Co 1/3 Mn 1/3 O 2 (NCM) active material. It is shown that the characteristic overpotentials duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 74 publications
8
121
0
Order By: Relevance
“…41-44 and 45; original research on the material can be found in Ref. [50][51][52][53][54][55][56][57][58][59][60]. In this work, we apply our thermodynamic modeling to Ni 0.6 Mn 0.2 Co 0.2 .…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41-44 and 45; original research on the material can be found in Ref. [50][51][52][53][54][55][56][57][58][59][60]. In this work, we apply our thermodynamic modeling to Ni 0.6 Mn 0.2 Co 0.2 .…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Recent investigations of this aspect of NMC can be found in References 58 and 59; see, in particular, Figure 5 of Ref. 58 and the associated discussion with respect to the inability to remove all Li from NMC at potentials yielding stable performance.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Fort he sameL iMO 2 -type electrode material, the amount of extracted Li + is proportional to the applied chargec ut-off potential;t hus,i tc an be concluded that the structural stability of LiMO 2 -type electrodesi sp rimarily determined by the amounto fe xtracted Li + ions. [16,22,23] In the literature,t he structural stability and stability versus transition-metal dissolution of various,t hat is,not the same cathode materials,positive electrode material has been compared and discussed as af unctiono ft he applied charge cut-off potential. [19,24,25] However, ac omparison between different LiMO 2 -type electrode materials with regard to their structural stability is only reasonable as af unction of the amount of extracted Li + ions.…”
Section: Introductionmentioning
confidence: 99%
“…NMC333 has been the focus of several articles related to synthesis, kinetic and transport properties estimation and performance rate study. 13,21 For NCM523, a few characterization studies have come out in the past decade. Yang et al 22 used Galvanostatic Intermittent * Electrochemical Society Student Member.…”
mentioning
confidence: 99%